Contrastive Analysis of French and Indonesian: A Review of Phonology, Morphology, and Syntax - Iim Siti Karimah; Yuliarti Murtiasih; Farida Amalia; Yoga Prima Putra; Yusuf Tri Herlambang; Iim Siti Karimah; Yuliarti Murtiasih; Farida Amalia; Yoga Prima Putra; Yusuf Tri Herlambang (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to analyze the similarities and differences between French language and Indonesian language through a contrastive analysis approach focusing on phonology, morphology, and syntax. At the phonological level, the main differences lie in the vowel and consonant systems, nasalization, stress patterns, and the pronunciation of final sounds. In terms of morphology, French exhibits a complex inflectional system, including verb conjugation and grammatical marking of gender and number, whereas Indonesian tends to be agglutinative, employing affixation without significant morphological changes based on gender or number. Syntactically, both languages generally follow a Subject–Predicate–Object (SPO) structure; however, they differ in noun phrase structure, article usage, agreement, and adjective placement. The findings indicate that these structural differences may cause linguistic interference in foreign language learning, particularly for Indonesian learners of French. This research is expected to contribute to the field of contrastive linguistics and foreign language teaching.